Influence of small-molecule material on performance of polymer solar cells based on MEH-PPV：PCBM blend - 刘晓东 徐征 张福俊 赵谡玲 张天慧 龚伟 宋晶路 孔超 闫光 徐叙瑢 (Chinese physics B, 2010)
In this work, the influence of a small-molecule material, tris（8-hydroxyquinoline） aluminum （Alq3）, on bulk heterojunction （BHJ） polymer solar cells （PSCs） is investigated in devices based on the blend of poly（2-methoxy-5-（2- ethylhexyloxy）-1,4-phenylenevinylene） （MEH-PPV） and [6,6]-phenyl-C61-butyric acid methyl ester （PCBM）. By doping Alq3 into MEH-PPV：PCBM solution, the number of MEH-PPV excitons can be effectively increased due to the energy transfer from Alq3 to MEH-PPV, which probably induces the increase of photocurrent generated by excitons dissociation. However, the low carrier mobility of Alq3 is detrimental to the efficient charge transport, thereby blocking the charge collection by the respective electrodes. The balance between photon absorption and charge transport in the active layer plays a key role in the performance of PSCs. For the case of 5 wt.% Alq3 doping, the device performance is deteriorated rather than improved as compared with that of the undoped device. On the other hand, we adopt Alq3 as a buffer layer instead of commonly used LiF. All the photovoltaic parameters are improved, yielding an 80% increase in power conversion efficiency （PCE） at the optimum thickness （1 nm） as compared with that of the device without any buffer layer. Even for the 5 wt.% Alq3 doped device, the PCE has a slight enhancement compared with that of the standard device after modification with 1 nm （or 2 nm） thermally evaporated Alq3. The performance deterioration of Alq3-doped devices can be explained by the low solubility of Alq3, which probably deteriorates the bicontinuous D-A network morphology; while the performance improvement of the devices with Alq3 as a buffer layer is attributed to the increased light harvesting, as well as blocking the hole leakage from MEH-PPV to the aluminum （Al） electrode due to the lower highest occupied molecular orbital （HOMO） level of Alq3 compared with that of MEH-PPV.